Undergraduate students' perceived mobile technology-learning barriers in their academic studies: a study in Greece - Kleopatra Nikolopoulou; Ioannis Tsimperidis; Avgoustos Tsinakos (Springer, 2023)
Abstract Mobile technology is used by undergraduate students for educational purposes, it supported students' learning during the pandemic, while mobile learning may have potential benefits and barriers. This study investigates Greek undergraduate students' perceptions on mobile technology-learning barriers in their academic studies. This topic is of international interest and still underexplored in Greece. An online questionnaire was completed by 212 students, and this study is descriptive-inferential. Students' perceptions regarding major barriers, reveal both external (internet connectivity issues, high cost of mobile devices, outdated operating system) and internal (tutors' negative attitudes and insufficient knowledge for mobile technology-learning integration) barriers. Other obstacles are associated with student concerns about distraction, and inadequate training opportunities to use mobile technology in their studies. Students' confidence, attitudes and digital skills regarding mobile technology adoption/use are perceived as minor barriers (or no barriers). The findings have implications for students, university tutors and university stakeholders.